Kajian Sistem Aktivitas pada Ruang Terbuka Publik Tepi Pantai Baron, Gunungkidul - Elisabet Nungky Septania; Ahmad Sarwadi; Dyah Titisari Widyastuti (Journal of Science and Applicative Technology, 2021)
Baron Beach is a public space that becomes an icon of Gunungkidul Regency. The conditions of a waterfront that have a river and surrounded by hills also the presence of fishing activities attract visitors. Various kinds of activities that occur in this public open space at the same time with different interests, can cause conflicts between activities even though there are also activities that are in line with each other. This research uses a qualitative descriptive method that compares data to utilized public open space during the research period with existing theories. As the unit of analysis are actors who use public open space and the physical conditions of open space. The purpose of this research is to identify activity patterns in utilizing public open space, so that they can be taken into consideration in planning and designing the Public Open Space of Baron Waterfront.